Hubungan antara dukungan emosional orangtua dan agresivitas remaja dengan orangtua bercerai - Dita Ridho Saqinah; Siti Suminarti Fasikhah; Uun Zulfiana (Cognicia, 2019)
The emergence of aggressive behavior in teenagers can occur due to various factors,  the family is one important aspect that is allegedly associated with the pattern adolescent aggressive behavior. The role of parents to adolescent aggressive behavior by providing emotional support needed to suppress aggressive behavior in adolescents themselves. The purpose of this study was to investigate the relationship between emotional support of parents and the aggressiveness of adolescents with divorced parents. The sampling technique used purposive technique with a subjects were 113 boys and girls with divorced parents aged 12 to 22 years, and lived with one parent. This research instruments using Agression Questionnair scale and the scale of parental emotional support made by the author based on aspects of emotional support by Thoits 1986 with data analysis using SPSS 21. The results show the value of (r) of -0.327 with p 0.000 < 0, 05. It shows that there is a significant negative correlation between parental emotional support and aggressiveness of adolescents with divorced parents. Parental emotional support’s contribution to adolescents with divorced parents aggressiveness of 10.7% (r2 = 0.107)